2012
DOI: 10.3329/jesnr.v5i1.11571
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality and Antibiogram of E. coli, Salmonella and Vibrio of Salad and Water from Restaurants of Chittagong

Abstract: The study aimed at examining the microbial quality of restaurant salad and the water used for salad preparation and their role as a source of antibiotic resistant bacteria. Samples were collected from 15 different restaurants located in Chittagong city. The range of Total Viable Count was 1.86×10 4 to7.28×10 5 CFU/g and 1.60×10 4 CFU/ml to 4.38×10 5 CFU/ml for salad and water respectively. Total colifrm and fecal coliform count > 1100 CFU/100 ml were found in 73.33% of salad and 33.33% water samples. Salmonell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
38
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 23 publications
5
38
2
Order By: Relevance
“…Again, most of the studies done in Bangladesh, concentrate on a single disease, pathogen, or specimen. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] But, a single organism can cause different types of infection, at different sites and can cause different diseases. For example, E. coli can cause gastroenteritis, sepsis, UTI, even meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…Again, most of the studies done in Bangladesh, concentrate on a single disease, pathogen, or specimen. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] But, a single organism can cause different types of infection, at different sites and can cause different diseases. For example, E. coli can cause gastroenteritis, sepsis, UTI, even meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the number of coliform bacteria in salads may reach 10 5 /g. Particularly, E.coli is one of the most isolated bacteria in salads (1)(2)(3)(4). E.coli shows many different serotypes and of these serotypes, E.coli O157:H7 is a significant morbidity and mortality cause for human health.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are usually accompanied with many food borne diseases, thus poses safety threats [3]. Ready to Eat (RTE) vegetables, generally grown near the metropolitan cities are cultivated in unhygienic environments [4], irrigated with poor quality water [5], and fertilized using organic and inorganic amendments [6,7]. This all leads to microbial contamination and spread of infectious diseases like diarrhoea, Salmonellosis and Shigellosis etc.…”
mentioning
confidence: 99%
“…Country wise list of RTE vegetables containing bacterial pathogens along with remedial measures have been listed by [12]. Comprehensive information on "Vegetable Microbiology" right from the sources of contamination to its consequences on human health is available in above mentioned literature [3][4][5][6][7][8][9][10][11][12].…”
mentioning
confidence: 99%
See 1 more Smart Citation